Kajar Ki Kothari - Khatri, Devakinandana (New Delhi Shivank Prakashan, 2022)
Not detective, not big Canvass Novel like Chandrakanta-Chandrakanta santati and Bhootnath but a milestone work, short novel based on the real life sketch of a man.
Keywords: Hindi fiction